Competence, Work Experience, And Integrity On The Performance Of Auditor : The Role Of Professionalism - Sigit Hermawan; Cindi Dwianti Roswita; Sarwenda Biduri; Ratna Nugraheni; Iffah Qonitah (Jurnal Reviu Akuntansi dan Keuangan, 2022)
This study aims to determine the effect of competence, work experience, and integrity on auditor performance with professionalism as an intervening variable. This study uses a quantitative approach. The sample in this study was 44 with purposive sampling technique. The population of this research are auditors who work in Public Accounting Firms in Surabaya. Data collection techniques using questionnaires with the help of validity and reliability tests. The data analysis technique used in this research is Partial Least Square (PLS). The results of this study indicate that (1) Competence has no significant effect on Auditor Performance, (2) Work Experience has no significant effect on Auditor Performance, (3) Integrity has a significant effect on Auditor Performance, (4) Competence has no significant effect on Professionalism, (5) Work Experience has a significant effect on Professionalism, (6) Integrity has a significant effect on Professionalism, (7) Professionalism has a significant effect on Auditor Performance, (8) Competence has no significant effect on Auditor Performance through Professionalism, (9) Work Experience has a significant effect on Auditor Performance through Professionalism, (10) Integrity has no significant effect on Auditor Performance through Professionalism.